1987
DOI: 10.1271/bbb1961.51.2395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of crocin, picrocrocin and safranal by saffron stigma-like structures proliferated in vitro.

Abstract: Crocin, picrocrocin, and safranal as the major secondary metabolites are important for the high quality of spice saffron. Crocin and picrocrocin were detected in stigma-like structures proliferated in vitro. Safranal appeared after heat treatment. The contents and relative ratio of these substances in the stigma-like structures were similar to those in intact young stigmas, indicating that these stigma-like structures showed not only morphological but also biochemical similarity to the intact stigmas. Saffron,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 0 publications
6
72
1
1
Order By: Relevance
“…We showed that while 2,4-D was essential in early adventitious shoot induction, it can be excluded from the culture media to enable further shoot development, which is consistent with a previous study [8]. On the other hand, the requirement of BAP as cytokinin for direct organogenesis of saffron was still essential as it was suggested in the literature [19,20,22]. It is well known that saffron is a recalcitrant species towards adventitious roots induction under in vitro conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We showed that while 2,4-D was essential in early adventitious shoot induction, it can be excluded from the culture media to enable further shoot development, which is consistent with a previous study [8]. On the other hand, the requirement of BAP as cytokinin for direct organogenesis of saffron was still essential as it was suggested in the literature [19,20,22]. It is well known that saffron is a recalcitrant species towards adventitious roots induction under in vitro conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In vitro production of stigma-like structures of saffron for the purpose of obtaining crocin, picrocrocin, and safranal was investigated by using different parts of the saffron plant such as corms [18], half ovaries [19][20][21], stigmas [22,23], petals and styles [23], anthers [24], stamens [25] and calli [26,27]. It is clear that majority of the in vitro studies were focused on the production of secondary metabolites through direct and indirect organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Eight stages of development have been defined for C. sativus stigmas based on the length of the tissue, pigmentation, and apocarotenoid content (Himeno and Sano, 1987). Stage II corresponds to a yellow undeveloped stigma and stage IV represents an orange undeveloped stigma.…”
Section: Identification Of Carotenoids In C Sativus Stigmasmentioning
confidence: 99%
“…Maximum number (120 indirectly and 20 directly) with 5.2 cm long of SLS were obtained in G-5 medium supplemented with 27μM NAA and 44.4μM BA (Table 3) followed by 100 indirectly and 20 directly with 4.5 cm long SLS on LS medium supplemented with 27μM NAA and 44.4μM BA ( Table 2). Development of stigma like structures from half ovaries on white medium supplemented with zeatin and NAA and half ovaries on different media using auxins has been reported (Fakhrai and Evans 1990;Himeno and Sano 1987). During this study the explants for the microcorm production and SLS have been standardized.…”
Section: Resultsmentioning
confidence: 99%